New block-labelled topological indices and physicochemical properties of heptane isomers - A. Uma Maheswari,; C. Ambika, (Utilitas Mathematica, 2025)
In this work, four new block-labelled topological indices, namely the block labelled product index, block labelled sum index, cluster block labelled product index, and cluster block labelled sum index, based on block label of the molecular structure, are defined. The new topological indices are investigated for Path and Star graphs in connection with AUM block mean labeling. In order to predict the physicochemical properties of heptane isomers, a comparative analysis is done, and the chemical applicability of these indices is determined for boiling point, vapour pressure, and enthalpy of vaporization. Through this work, we bridge the concept of AUM block mean labeling to the block- labelled topological indices. Also, these newly introduced indices are compared with other degree-based indices.